Reflection high-energy electron diffraction patterns of carbide-contaminated silicon surfaces - Long, Robert G., author; Becker, James P., author; Mahan, John E., author; American Vacuum Society, publisher (Colorado State University. Libraries, 1994)
Carbon contamination of silicon surfaces is a longstanding concern for growers of thin films who utilize silicon wafer substrates. This contamination often takes the form of epitaxial β-SiC particles which grow after the decomposition of adsorbed carbon-bearing molecules, and the subsequent reaction of the freed carbon with the silicon substrate. Positive identification of such SiC contamination is possible via reflection high-energy electron diffraction (RHEED). To provide a complete demonstration and analysis of the relevant RHEED patterns, we prepared within a "silicon molecular beam epitaxy" system carbide-contaminated silicon surfaces using procedures intended to foster such contamination. With conventional RHEED instrumentation, we obtained transmission electron diffraction patterns which resulted from the passage of the RHEED electron beam laterally through the SiC particles. Comparison with theoretically predicted patterns positively identifies the β-SiC phase and shows that the particles are epitaxially aligned, with their cubic axes parallel to those of the substrate. {This finding is in agreement with the widely accepted model for the behavior of carbon on silicon surfaces [Henderson et al., J. Appl. Phys. 42, 1208 (1971)]}. More typically during in-situ silicon substrate preparation for thin film growth, RHEED patterns indicating such contamination contain SiC spots which are mere vestiges of the complete transmission diffraction patterns presented in this work.